(untitled) (Ciencia Veterinaria, 2017)
Horsemeat is an important economic resource for our country, as Argentina is considered one of the leading world exporters of horsemeat. But there is little research about the quality of it. It was examined the effect of: (i) storage temperature (0, 4ºC) and (ii) gaseous permeability of the packaging film (polyethylene and EVA SARAN EVA for vacuum packaging) on the growth of bacteria (Total Aerobic Mesophilic Heterotrophic Bacteria, Enterobacteriaceae and Pseudomonas sp.) isolated from horse muscle. Microbial growth was modelled using Gompertz or the Linear Regression Models. The lowest final bacteria counts were obtained with the combination of 0ºC and vacuum packaging. At higher temperatures, 4ºC, there were no significant differences (p<0.05) among the final counts in relation to both films. The lowest values of µ (microbial growth rate) for the development of studied microorganisms were observed in samples stored in EVA SARAN EVA DOI:http://dx.doi.org/10.19137/cienvet2013-1515